Effect of Bamboo Dance Learning Model and Early Ability Against Habit of Mind Mathematical Students - Waryadi Waryadi; Kadir Kadir; Wardani Rahayu (Lembaga Penelitian dan Pengabdian Masyarakat Universitas Nahdlatul Ulama Blitar, 2019)
Based on the results of the preliminary study, Mathematical habits of mind (MHoM) mathematics students are generally still weak.Therefor, efforts are needed to overcome them. One way is to choose and apply the appropriate learning model. This study aims to determine whether the Bamboo Dance learning model and Early Mathematical Ability of Students can significantly influence the mathematics MHoM of students. This research is using the experimental method. Involving VII grade students of junior high school, with experimental classes and control classes as many as 36 student samples. The experimental class was given learning by applying the Bamboo Dance learning model, while the control class with conventional learning. The results of the study showed that the MHoM mathematics of experimental class students as a whole was better than the control class with a significance level of 0.023. Likewise, for groups of students with high and moderate initial abilities in the experimental class it is better than the group of students with high and moderate initial abilities in the control class, with a significance level of 0.011 and 0.025 respectively. Whereas for the group of students with low initial abilities there was no significant effect of the Bamboo Dance learning model on the ability of the MHoM students with a significance level of 0.775.